How Effective Are Pictorial Warnings on Tobacco Products? New Evidence on Smoking Behaviour Using Australian Panel Data - Daniel Kühnle (Institute of Labor Economics (IZA), 2019)
Studies examining the introduction of pictorial warnings on cigarette packages provide inconclusive evidence due to small samples and methodological issues. We use individual-level panel data from Australia to examine the association between pictorial warnings and smoking behaviour - prevalence, quitting, initiating and relapsing. The pictorial warnings were accompanied by a reference to a smoking cessation helpline and supportive television commercials. Applying an event study framework, we show that the reform reduced smoking rates by around 4% within the first year of the policy. The effect decreases with age, is similar for men and women, and is slightly larger for low-educated compared to high-educated individuals. The reform permanently lowered smoking rates primarily due to increased quitting in the year of the reform. Thus, pictorial warnings combined with a reference to a smoking cessation helpline and supportive media campaigns are an important tobacco control measure to reduce the social costs of smoking.
Keywords: I12; I14; I18; 330; pictorial warnings; smoking; cessation; smoking initiation; smoking relapse